Preferências de atividade física em adultos brasileiros: resultados da Pesquisa Nacional de Saúde - Wendt, Andrea (2019)
This study aims to verify the distribution of different types of practices in Brazilian adults according to sociodemographic variables. Cross-sectional study using data from the National Health Survey (PNS) of 2013 including individuals with 18 years or more practitioners of physical activity (n = 17,350). Independent variables were sex, age, education and geographic regions. The dependent variables were the types of physical activity more frequent in the population. To present frequencies according to region, education and age types of physical activity were classified in three groups: walking, exercise and sports. The data were analyzed in STATA 12.1 using the svy command. Among men, the most common activities were soccer (39.1%), walking (22.9%) and bodybuilding (15.3%). Among women, were walking (48.9%), gymnastics (19.2%) and bodybuilding (14.2%). Among men, walking was higher in older individuals, with no education and in the Midwest region (p < 0.001). For exercise, among men, the habit was more common among younger, with higher education and the Southeast (p < 0.001). Regarding sports, the practice was more common among the younger ones, with higher schooling and the Northern region (p < 0.001). The associations for women were similar to associations for men. The types of physical activity have influence of age, education and region of country. These aspects should be considered in interventions planning. More studies are necessary to understand the motivators to choose each practice.